Modelo de Maturidade Lean-Circular para autoavaliação em empresas - Silva, Marina Hernandes de Paula (Universidade Federal de São Carlos, 2023)
Economic and environmental efficiency are necessary guidelines in the production management of companies today. Lean Manufacturing (LM) integrated with the concepts of Green/Sustainable Manufacturing has been shown effective in reducing costs, waste, and environmental impacts, increasing efficiency in the use of resources, in addition to contributing to improve productivity, quality and added value to customers. However, there is still a lack of a holistic views on such integration, looking at the entire life cycle of processes, products and/or the organizational level. The integration of LM with Circular Economy (CE) can bring this view into practice, however, there are few studies that address this issue so far. Implementing LM with CE and making companies’ processes, products, and the life cycle leaner and more circular, requires a clear vision of the practical aspects to be taken. Maturity Models are relevant in that way as they can help companies understand where they are and what they need to do to advance to the next levels. Therefore, this paper aims to develop a maturity model for the self-assessment of companies regarding the implementation of LM and CE in their processes, products and in life cycle perspective as well. The development was carried out based on the steps of design science research, creating a Lean-Circular Maturity Model (LCMM). After the development phase, the LCMM was validated with 13 experts and applied in practice to 09 Brazilian companies in the primary economy sectors (1 in the Southeast region, 1 in the Midwest, and 1 in the North), secondary (4 in the Southeast region and 1 in the center-west) and tertiary (1 from the south region). The results of the LCMM application showed that some companies are looking for cleaner and more sustainable alternatives before understanding and mapping their value stream (occurred in up to 66% of the companies), thus being able to cause errors in the planning and hierarchization/prioritization of actions of improvement. In addition, the lack of training and awareness of all employees regarding the efficient use of resources was present in 61% of the evaluated companies. Also is highlighted the lack of initiatives related to the management of efficient use of resources in the life cycle of products, which is one of the main opportunities observed. Also highlighted is the lack of initiatives related to the management of efficient use of resources in the life cycle of products, which is one of the main opportunities observed. Thus, the LCMM self-assessment model can be easy to apply, provides fast self-diagnosis, and the secondary sector (manufacturing industries) can be the most benefited from its use. As conclusion, the developed model contributes to the literature on maturity models by combining LM and CE theories with the process, product and lifecycle perspectives, making it possible to replicate the proposed step-by-step for other areas of study. As a limitation, the study does not address the social aspect, this approach being possible in future studies.
Lean-Circular Maturity Model for self-assessment in companies
Keywords: Nível de Maturidade; Produção Enxuta; Sustentabilidade; Berço-ao-berço; Circularidade; Maturity Level; Lean Manufacturing; Sustainability; Cradle-to-cradle; Circularity; ENGENHARIAS::ENGENHARIA DE PRODUCAO